Comparative analysis of retinal photoplethysmographic spatial maps and thickness of retinal nerve fiber layer - Odstrcilik, Jan; Kolar, Radim; Horn, Folkert; Tornow, Ralf-Peter (PLoS One, 2023)
The paper presents a comparative study of the pulsatile attenuation amplitude (PAA) within the optic nerve head (ONH) at four different areas calculated from retinal video sequences and its relevance to the retinal nerve fiber layer thickness (RNFL) changes in normal subjects and patients with different stages of glaucoma. The proposed methodology utilizes processing of retinal video sequences acquired by a novel video ophthalmoscope. The PAA parameter measures the amplitude of heartbeat-modulated light attenuation in retinal tissue. Correlation analysis between PAA and RNFL is performed in vessel-free locations of the peripapillary region with the proposed evaluating patterns: 360° circular area, temporal semi-circle, nasal semi-circle. For comparison, the full ONH area is also included. Various positions and sizes of evaluating patterns in peripapillary region were tested which resulted in different outputs of correlation analysis. The results show significant correlation between PAA and RNFL thickness calculated in proposed areas. The highest correlation coefficient Rtemp = 0.557 (p<0.001) reflects the highest PAA-RNFL correspondence in the temporal semi-circular area, compared to the lowest value in the nasal semi-circular area (Rnasal = 0.332, p<0.001). Furthermore, the results indicate the most relevant approach to calculate PAA from the acquired video sequences is using a thin annulus near the ONH center. Finally, the paper shows the proposed photoplethysmographic principle based on innovative video ophthalmoscope can be used to analyze changes in retinal perfusion in peripapillary area and can be potentially used to assess progression of the RNFL deterioration.
Keywords: Glaucoma; optická koherentní tomografie; Nerve Fibers; lidé; nervová vlákna; Retinal Ganglion Cells; Tomography, Optical Coherence; glaukom; retinální gangliové buňky; discus nervi optici; Optic Disk; Humans